Effect of Joule heating on the reliability of solder joints under power cycling conditions. (September 2018) - Mei, J.; Haug, R.; Lanier, O.; Grözinger, T.; Zimmermann, A.
Abstract: In the field, electronic devices are often experiencing switching cycles. With the trend of miniaturization and electrification, automotive electronic packages are facing increasingly critical reliability issues regarding current stressing and the accompanying Joule heating. In this work, the load capability of two surface-mounted shunt components subjected to cyclic current pulses is investigated. Asymmetric self-heating due to the Peltier effect is observed with infrared thermography in one of the shunt components, which leads to polarity in the microstructural evolution influencing the failure mode in the solder joint. Finite element method (FEM) is utilized to simulate the coupled electrical, thermal and mechanical fields in the assembly and to assess the response of the solder joints exposed to power cycling. Lifetime data are collected and statistically analysed based on the Weibull distribution. Highlights: Reliability of SAC solder joints subjected to power cycling has been investigated experimentally and numerically. An asymmetric failure mode of solder joints due to Peltier effect has been observed. Thermal fluctuations induced from the self-heating of shunts highly influence the microstructural evolution of solder joints. The accumulated plastic strain during each cycle is simulated, which corresponds well with the lifetime data. The risk for electromigration is also evaluated in the paper.